2022
DOI: 10.1002/jad.12076
|View full text |Cite
|
Sign up to set email alerts
|

Peer sexual harassment, affect, and substance use: Daily level associations among adolescents

Abstract: Introduction Peer sexual harassment is associated with adolescent substance use at the global level; however, it is unknown whether substance use occurs proximal in time to the sexual harassment experience. This study used daily reports to examine the proximal relations between sexual harassment victimization and affect and substance use. Based on theories of self‐medication, we hypothesized that negative affect and substance use (cigarettes, electronic cigarettes, alcohol, and marijuana) would be higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 74 publications
0
3
1
Order By: Relevance
“…Adolescents who experience sexual harassment also may be using alcohol to cope with negative affect resulting from the harassment. Daily level data collected from a subsample of adolescents from the present study revealed that experiencing sexual harassment was associated with same day sadness and alcohol use, suggesting that alcohol may be used as a coping mechanism; however, the temporal ordering within day could not be established (Livingston et al, 2022). There is also evidence from college samples showing that there are reciprocal effects with sexual harassment predicting negative affect and alcohol use, which in turn renders individuals vulnerable to future sexual harassment (Wolff et al, 2017).…”
Section: Sexual Harassment Victimization Class Membership and Alcohol...contrasting
confidence: 69%
“…Adolescents who experience sexual harassment also may be using alcohol to cope with negative affect resulting from the harassment. Daily level data collected from a subsample of adolescents from the present study revealed that experiencing sexual harassment was associated with same day sadness and alcohol use, suggesting that alcohol may be used as a coping mechanism; however, the temporal ordering within day could not be established (Livingston et al, 2022). There is also evidence from college samples showing that there are reciprocal effects with sexual harassment predicting negative affect and alcohol use, which in turn renders individuals vulnerable to future sexual harassment (Wolff et al, 2017).…”
Section: Sexual Harassment Victimization Class Membership and Alcohol...contrasting
confidence: 69%
“…Female students in particular welcomed the inclusion of sexual harassment as an intervention target and indicated that it occurred both inside and outside of school. Sexual harassment victimization has been linked prospectively with a variety of negative outcomes, including depression, eating disorders, substance use and increased risk for dating and sexual violence, underscoring the importance of preventing this form of peer aggression (Chiodo et al, 2009;Davis et al, 2018;Livingston et al, 2022Livingston et al, , 2023.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of research shows that experience of sexual violence and harassment in childhood is associated with a higher prevalence of smoking tobacco and other substance abuse [62][63][64][65][66]. In Africa, there is a shortage of studies exploring the association between whatever form of tobacco use and experience of sexual violence [67].…”
Section: Influential Factorsmentioning
confidence: 99%